مقارنة بين طريقتي الحذف وطريقة الإمكان الأعظم للمعلومات الكاملة في معالجة البيانات غير التامة لمتغيرات أنموذج الانحدار المتعدد - المتولى، أحمد شاكر; سلمان، منار جبار (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2018)
The problem of incomplete data for the variables of the multiple regression model is one of the most important problems faced by the researcher in the process of collecting data for the variables of research This is due to several reasons, including controlled reasons such as cost and risk and because of the lack of the possibilities for inspection and other are uncontrolled, such as cases of damage when the tests or loss due to wars or disasters , That the adoption of such incomplete data in the analysis leads to inaccurate results and therefore the loss of data should be addressed by using some methods of treatment that lead to accurate results or near precision. The study dealt with two methods of incomplete data processing for regression model variables list wise deletion methoed (LD) and FULL information maximum likelihood methoed (FIML). The aim of study is to compare these two methods in order to arrive at the best method based on simulations. The results of the simulation experiments revealed that the method of deletion is better than the method of maximizing the full information in the processing of incomplete data, based on the mean error squares of the estimated regression model.
تعد مشكلة البيانات غير التامة لمتغيرات أنموذج الانحدار المتعدد واحدة من أهم المشاكل التي تواجه الباحث عند عملية جمع البيانات لمتغيرات البحث ويعود ذلك إلى عدة أسباب منها أسباب مسيطر عليه مثل الكلفة والمخاطرة وبسب عدم توفير الإمكانيات للمعاينة وأخري تكون غير مسيطر عليها مثل حالات التلف عند إجراء التجارب أو الفقدان بسبب الحروب أو الكوارث، إن اعتماد مثل هذه البيانات غير التامة في عملية التحليل تؤدي إلى نتائج غير دقيقة وعليه يتوجب معالجة فقدان البيانات موضوع البحث باستعمال بعض طرائق المعالجة التي تؤدي إلى الحصول على نتائج دقيقة أو تقترب من الدقة. تناول البحث طريقتين من طرائق معالجة البيانات غير التامة لمتغيرات أنموذج الانحدار هما، طريقة الحذف (list wise deletion)، وطريقة الإمكان الأعظم للمعلومات الكاملة FULL information maximum likelihood)) (FIML)، يهدف إلى إجراء مقارنة بين هاتين الطريقتين للتوصل إلى أفضل طريقة بالاعتماد على تجارب المحاكاة أفرزت نتائج تجارب المحاكاة، إلى أن طريقة الحذف أفضل من طريقة الإمكان الأعظم للمعلومات الكاملة في معالجة البيانات غير التامة وذلك بالاعتماد على متوسط مربعات الأخطاء لأنموذج الانحدار المقدر، كمعيار للمفاضلة.
Keywords: الأساليب الاحصائية -- التحليل الاحصائى -- معالجة البيانات -- نماذج الإنحدار